2006
DOI: 10.1074/jbc.m510085200
|View full text |Cite
|
Sign up to set email alerts
|

Transient IκB Kinase Activity Mediates Temporal NF-κB Dynamics in Response to a Wide Range of Tumor Necrosis Factor-α Doses

Abstract: Dynamic properties of signaling pathways control their behavior and function. We undertook an iterative computational and experimental investigation of the dynamic properties of tumor necrosis factor (TNF)␣-mediated activation of the transcription factor NF-B. Surprisingly, we found that the temporal profile of the NF-B activity is invariant to the TNF␣ dose. We reverse engineered a computational model of the signaling pathway to identify mechanisms that impart this important response characteristic, thus pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
145
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(157 citation statements)
references
References 42 publications
12
145
0
Order By: Relevance
“…Subsequent experimental studies have supported these predictions. Although a TNF dose-response study showed that even 0.1 ng/ml, about 100-fold lower than commonly used concentration of this cytokine, can produce strong NF-kB activity (Cheong et al, 2006), persistent or pulse stimulation with TNF produce remarkably different gene expression programs (Hoffmann et al, 2002).…”
Section: Transcriptional Specificity As Determined By Nf-jb Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent experimental studies have supported these predictions. Although a TNF dose-response study showed that even 0.1 ng/ml, about 100-fold lower than commonly used concentration of this cytokine, can produce strong NF-kB activity (Cheong et al, 2006), persistent or pulse stimulation with TNF produce remarkably different gene expression programs (Hoffmann et al, 2002).…”
Section: Transcriptional Specificity As Determined By Nf-jb Dynamicsmentioning
confidence: 99%
“…Typical representatives TNF-R1 and TLR4, which mediate TNF and LPS signaling, respectively, were found to produce remarkably different IKK induction profiles (Werner et al, 2005), which in the case of TNF are independent of the stimulus concentration (Cheong et al, 2006). A current research focus is the elucidation of the mechanisms that produce stimulus-specific IKK activities.…”
Section: Transcriptional Specificity As Determined By Nf-jb Dynamicsmentioning
confidence: 99%
“…This can easily be verified by removing the equation for x 3 from Eqs. (5). The resulting two-dimensional model leads to two monotonously decreasing FTLs.…”
Section: Gene Transcription Networkmentioning
confidence: 94%
“…While steady state processes are most important in metabolic systems [1], transient dynamics play an important role in cell communication [2,3,4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation